Analisis Pendekatan Keadilan Restoratif dalam KUHP dan KUHAP Baru: Peluang dan Tantangan Implementasinya - jihan Jihan Fajrilia (Jurnal Hukum Lex Generalis, 2026)
This study examines the integration of restorative justice under Law Number 1 of 2023 on the Criminal Code, as amended by Law Number 1 of 2026 and Law Number 20 of 2025 on Criminal Procedure. Using normative legal research, it analyzes sentencing purposes, sentencing guidelines, eligibility, procedural stages, exclusions and judicial oversight. The Criminal Code provides the substantive foundation, while the Criminal Procedure Code establishes an integrated mechanism from investigation to trial. Opportunities include victim restoration, legal certainty and reduced imprisonment. Challenges concern harmonizing sectoral rules, law-enforcement capacity, unequal bargaining positions and consistent judicial supervision.